NAVIGATING MODERN WARFARE CHALLENGES: A REVIEW OF THE EVOLUTION OF INTERNATIONAL HUMANITARIAN LAW IN THE CONTEXT OF CYBERWARFARE - Shafiq, Ur Rahman; Mahmood, Ahmed Shaikh; Muhammad, Tahir; Imran, Naseem; Sriyanto, Sriyanto; Nur Fatihah, Abdullah Bandar; Khalid, Zaman (Southwest Jiaotong University, 2024)
The need for states to discuss treaty making in the domain of cyberwarfare emerges out the complexities and obstacles concerning cyber operations. The Tallinn Handbook provides valuable guidance, but it is not a treaty, hence the manual is not a binding document. There can be differing interpretations and practices among states regarding bringing international law to disputes involving cyberspace. To address these discrepancies and encourage more collaboration in the cyber activities, there is a growing recognition of the need for states to engage in discussions and negotiations on the establishment of treaties around the world specific to the ware fare on cyber space. Treaty-making can bring a more concrete and binding governance to elucidate the States’ rights and obligations, uphold transparency, and create standards of conduct in cyberspace. This study offers a thorough analysis of the evolutionary trajectory of Int’l Humanitarian Law (IHL) solving the problems resulted from innovative modes of the warfare. It explicitly focuses on the regulation of cyber warfare, identifying and evaluating key provisions and mechanisms within IHL relevant to this context. The research assesses the adequacy of existing IHL provisions in effectively governing cyber warfare and proposes essential advancement or amendments to address the gaps in law and complications connected to this evolving from the issues therein. The study aims to offer insights into how IHL can adapt to the demands of the modern-day battlefield, significantly in the domain of cyber warfare. Two potential paths can be underscored for resolution of the issue in hand: the creation of a dedicated treaty for cyber-armed conflicts or the evolution of state practices into binding customs. In this evolving landscape, interpreting existing IHL provisions and their utilization in cyberwarfare remains crucial, maintaining alignment with the underlying humanitarian principles of IHL. The study initially anticipates continued engagement in damaging cyber conflicts driven by a cyber-arms race, which might ultimately lead to the development of new norms, albeit over an extended period. The treaty making efforts are the best way to deal with the situation provided state parties to IHL make a collaborative endeavor in this behalf.